2015
DOI: 10.1590/0104-07072015000670014
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Temporary Catheter-Related Infection in Patients on Dialysis Treatment

Abstract: ABSTRACT:This study aims to identify risk factors associated with temporary hemodialysis catheter-related infection, in patients on dialysis treatment in a teaching hospital. This is a prospective study performed from November of 2012 to May of 2013, with 129 patients. Sociodemographic, clinical and biochemical data were collected from patient charts. In patients with a catheter,, 48.8% had catheter-related infection, 65% were male, 65% were 60 years of age or older, 85.3% had the catheter because they were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
2
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 22 publications
1
6
2
8
Order By: Relevance
“…The mean duration of catheterization was 8.53 (± 4.97) days and 75% of the patients who developed infection remained with the catheter for more than 7 days. In the present study, the mean duration of catheterization was not related to the occurrence of the outcome, but other studies in the literature present a higher mean duration (8) . The short-term hemodialysis catheter should only be used in emergency situations in hospitalized patients and should remain for up to seven days, according to the recommendations of the Kidney Disease Outcomes Quality Initiative (16) .…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…The mean duration of catheterization was 8.53 (± 4.97) days and 75% of the patients who developed infection remained with the catheter for more than 7 days. In the present study, the mean duration of catheterization was not related to the occurrence of the outcome, but other studies in the literature present a higher mean duration (8) . The short-term hemodialysis catheter should only be used in emergency situations in hospitalized patients and should remain for up to seven days, according to the recommendations of the Kidney Disease Outcomes Quality Initiative (16) .…”
Section: Discussioncontrasting
confidence: 64%
“…The latter characteristic showed an increased risk of infection. The other characteristics did not present a significant relationship with the occurrence of the outcome, as in other studies found in the literature (4,8,10) . Smoking and alcohol consumption were also reported by patients who developed infection, and those who consumed alcohol had a higher risk of infection than the others.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Elderly patients with acute renal failure and chronic renal failure, are more likely to purchase catheters infections due to access to dialysis procedures [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Complicações de cateter e outras relacionadas a inadequada orientação e manejo do paciente na hemodiálise são responsáveis por elevado número de morbimortalidade e dispêndio de recursos públicos que poderiam ser evitados (Borges;Bedendo, 2015). Research, Society andDevelopment, v. 9, n. 10, e8429109003, 2020 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v9i10.9003 Para Sousa et al (2013), os principais eventos adversos presentes em hemodiálise são: cateter obstruído, retirada acidental da agulha e coagulação do sistema extracorpóreo advindos respectivamente das condições do paciente, das condutas profissionais e organização do serviço.…”
unclassified